If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + 2 = 3m + -4 Reorder the terms: 2 + m = 3m + -4 Reorder the terms: 2 + m = -4 + 3m Solving 2 + m = -4 + 3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3m' to each side of the equation. 2 + m + -3m = -4 + 3m + -3m Combine like terms: m + -3m = -2m 2 + -2m = -4 + 3m + -3m Combine like terms: 3m + -3m = 0 2 + -2m = -4 + 0 2 + -2m = -4 Add '-2' to each side of the equation. 2 + -2 + -2m = -4 + -2 Combine like terms: 2 + -2 = 0 0 + -2m = -4 + -2 -2m = -4 + -2 Combine like terms: -4 + -2 = -6 -2m = -6 Divide each side by '-2'. m = 3 Simplifying m = 3
| -3(-5x-1)+4x-3=1 | | 1/4-b=1/2 | | y(x)=4x | | -17-2=7-10x | | 0.66x+5=0.75x-6 | | 4c=dforc | | 2-2/3 | | 3/4-b=11/8 | | -3.6x=-35.28 | | 11(v+2)-2v=3(3v+4)-16 | | 0.66+5=0.75-6 | | 5=5(x-3)+4-4x | | x-y+3x+4y=14 | | xsqared-13+36=0 | | 2/3-b=3 | | 1/2+7/8 | | 4/5x-1/16 | | 5x-5=x+3 | | 5/2a-3-3/2a=2 | | 7x-6=3(2x+5)-9 | | 2/7=x/49 | | 9q^2-25=0 | | x/5=x-8 | | 1+1/x=30/x^2 | | 6x-49=0 | | x+2y+6x-y=14 | | 49-3x=15x+23 | | f(x)=4x^2+4x+36 | | -.10(6)+.10x=.05(x-8) | | 2/5p+4=8 | | 1/50=x/210 | | -7x+3=-8x-9 |